2017
DOI: 10.18632/oncotarget.19080
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of Gli1 expression in breast cancer: a meta-analysis

Abstract: Glioma-associated oncogene 1 (Gli1) is a critical transcriptional factor of Sonic hedgehog pathway which has been proved to participate in the initiation and progression of tumor in mammalians. However, its clinical value in breast cancer remains unknown. Thus, a meta-analysis was performed to clarify the association of Gli1 over-expression, clinic-pathological characteristics, molecular subtypes and prognosis in breast cancer. According to included criteria, 13 eligible studies containing 2816 patients all ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 48 publications
1
24
1
1
Order By: Relevance
“…A positive association was noted between increased GLI1 expression, tumor stage, and lymph node status, correlating with an unfavorable overall survival (OS) [25]. A subsequent meta-analysis confirmed that GLI1 overexpression in breast cancer is associated with reduced disease-free survival, 3-and 5year survival, and OS [26].…”
Section: Introductionmentioning
confidence: 83%
“…A positive association was noted between increased GLI1 expression, tumor stage, and lymph node status, correlating with an unfavorable overall survival (OS) [25]. A subsequent meta-analysis confirmed that GLI1 overexpression in breast cancer is associated with reduced disease-free survival, 3-and 5year survival, and OS [26].…”
Section: Introductionmentioning
confidence: 83%
“…Besides, YB1 could positively regulate the expression of epidermal growth factor receptor (EGFR) and human epidermal growth factor receptor 2 (HER2) and promote the proliferation of breast cancer cells . Wang et al also found a significant correlation between YB1 expression and HER2 positivity. In lung adenocarcinoma cells, Ha et al demonstrated that YB1 could promote the EMT mediated by transforming growth factor beta 1 (TGF‐β1) and promote the invasion and metastasis of cancer cells .…”
Section: Discussionmentioning
confidence: 99%
“…YB-1, a member of the cold-shock protein family, seems to be part of the regulation of several signaling cascades affecting cellular proliferation, survival and invasion [33]. It is frequently expressed in various tumors including the non-small cell lung carcinoma [34] or the mammary carcinoma, where it might have prognostic value [35]. Its nuclear as well as cytoplasmic expression in breast cancer was previously reported [36, 37].…”
Section: Discussionmentioning
confidence: 99%
“…Further analyses of the YB-1 expression in our TNBC cohort, revealed a significant correlation with the histological grade of the tumors. Wang and colleagues found no statistical association with the histological grade but an association of YB-1 expression and a bad prognosis for a 5-year-overall survival [35]. Such an association of YB-1 expression and bad prognosis for 5-year-survival was shown previously in a smaller cohort suggesting a prognostic and predictive role for YB-1 in breast cancer [35, 37]; however, the relevance of YB-1 for TNBC was not explicitly analyzed.…”
Section: Discussionmentioning
confidence: 99%